2018
DOI: 10.1038/s41467-018-07706-9
|View full text |Cite
|
Sign up to set email alerts
|

Single crystal hybrid perovskite field-effect transistors

Abstract: The fields of photovoltaics, photodetection and light emission have seen tremendous activity in recent years with the advent of hybrid organic-inorganic perovskites. Yet, there have been far fewer reports of perovskite-based field-effect transistors. The lateral and interfacial transport requirements of transistors make them particularly vulnerable to surface contamination and defects rife in polycrystalline films and bulk single crystals. Here, we demonstrate a spatially-confined inverse temperature crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
266
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(272 citation statements)
references
References 60 publications
4
266
2
Order By: Relevance
“…Therefore, the resultant built-in potential in the device channel is determined by the Schottky barrier height difference between two opposite MW-metal contacts. [41] As a result, a built-in potential with the direction from MW (Ag) to Au (MW) is formed near the MW-Au (MW-Ag) contact. In this case, the photocarriers (induced by light absorption with a photon energy higher than perovskite bandgap) have no preferred drift direction in the channel, or in other words, the photocurrent is opposite and antisymmetric near both MW-metal contacts, leading to zero net photocurrent.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the resultant built-in potential in the device channel is determined by the Schottky barrier height difference between two opposite MW-metal contacts. [41] As a result, a built-in potential with the direction from MW (Ag) to Au (MW) is formed near the MW-Au (MW-Ag) contact. In this case, the photocarriers (induced by light absorption with a photon energy higher than perovskite bandgap) have no preferred drift direction in the channel, or in other words, the photocurrent is opposite and antisymmetric near both MW-metal contacts, leading to zero net photocurrent.…”
Section: Resultsmentioning
confidence: 99%
“…Thin-Film: CH 3 NH 3 PbI 3−x Cl x [32,33,104,105,110,111,113,[120][121][122] has been investigated as semiconductor in FETs. Chin et al [102] fabricated a FET by using CH 3 NH 3 PbI 3 as channel and 500 nm SiO 2 layer as the dielectric layer.…”
Section: Lead (Ii)-based Perovskite Materials As Semiconductormentioning
confidence: 99%
“…The transport was limited by ion migration caused by point defects and grain boundaries, the polarization disorder of the MA + cations, and the thermal vibrations of the lead halide inorganic cages. [108] Yu et al [113] demonstrated a FET device based on micrometer-thin MAPbX 3 (X = Cl, Br, I) single crystal as the semiconductor. In PEIE-treated devices, the electron mobility values reached 5 cm 2 V −1 s −1 at 100 K and 3 cm 2 V −1 s −1 at room temperature.…”
Section: Lead (Ii)-based Perovskite Materials As Semiconductormentioning
confidence: 99%
See 2 more Smart Citations